Survei VS Quick Count (Studi Kasus Pemilukada DKI Jakarta Putaran 1) - Akhmad Fauzy (Unisia, 2012)
Purpose of this research is to compare the results of the survey and a quick count on election province DKI Jakarta 2012 on round 1. institute survey that wiil compare the results of the survey and its quick count is the Lingkaran Survei Indonesia, IndoBarometer and Jaringan Suara Indonesia. There are significant differences between the survey results and the quick count survey of three institutions.Key words: election, survey, quick count